Os traços aspectuais condicionantes da alternância causativo-incoativa do português brasileiro - Maria Jose de Oliveira (2016)
This thesis aims to describe and investigate the conditioning features of causative-inchoative alternation in Brazilian Portuguese. The research begins with the hypothesis that the aspectual features of affixes of verbs of these structures are the ones that allow such alternation. For instance, apodrecer rot: O calor apodreceu a maçã The heat rotted the apple brings about the change a maçã tornou-se podre the apple became rotten. Under this condition, the verb apodrecer rot also participates in the intransitive construction the apple rotted. By the change imposed on the internal argument (e.g.: a maçã the apple), this type of verb is generally termed change-of-state verb. With this information, I defend the hypothesis that the causative-inchoative alternation emerges from the nature and combination of the features of change of state verbs licensed in abstract morphemes and organized into syntactic terminals, as supported by the Distributed Morphology (henceforth DM). In these morphemes are inserted the following vocabulary items: the root and the affixes {a-/en-/es-...-ec-}. Therefore, the conditions for the formation of the verbs analyzed are: (i) the root specified for dynamicity; (ii) the projection of a syntactic terminal, labeled ASP, whose head has the features [+DYNAMIC, +INCHOATIVE], motivated by the affixes {a-/en-/es-...-ec-}. The prefixes {a-/en-/es-} perform the feature [+DYNAMIC], and the suffix {-ec-} performs the feature [+INCHOATIVE], which projects the internal argument with the feature [+CHANGE OF STATE]; (iii) the verbalizer (labeled v1) which categorizes the compound formed by the root and the aspectual prefixes carries the feature [±AGENT], which connects itself to the external argument of the constructions in analysis; (iv) a telic construction results from this operation. The analyzed data are mainly collected from the following works: Rio-Torto (2004), Cançado, Godoy, and Amaral (2013), Bassani (2013), as well as from Portuguese language dictionaries. For the development of the analysis, I adopt the premises of DM combined with some insights of the Event Structures.